2020
DOI: 10.1108/rpj-07-2019-0193
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 3D printed guide for orbital implant

Abstract: Purpose Extrinsic trauma to the orbit may cause a blowout or orbital fracture, which often requires surgery for reconstruction of the orbit and repositioning of the eyeball with an implant. Post-operative complications, however, are high with the most frequent cause of complications being a mismatch of the position and shape of the implant and fracture. These mismatches may be reduced by computed tomography (CT) based modeling and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The production of prostheses is often expensive and requires complex intraoperative processes. Individual fabrication of implants using 3D-CAD methods allows for precise and anatomical reconstruction in a shorter operating time compared to other conventional techniques [10][11][12][13][14].…”
Section: Analysis Of Facial Implants Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of prostheses is often expensive and requires complex intraoperative processes. Individual fabrication of implants using 3D-CAD methods allows for precise and anatomical reconstruction in a shorter operating time compared to other conventional techniques [10][11][12][13][14].…”
Section: Analysis Of Facial Implants Modelmentioning
confidence: 99%
“…The largest surface area within this scale was found in the MED610 material model. This means that despite the deformations, it is closest to the intended dimensions [14][15][16][17]. The utilization of additive technologies in the production of medical models, both for direct therapeutic purposes and educational purposes, has expanded these individual areas.…”
Section: Analysis Of Facial Implants Modelmentioning
confidence: 99%
“…They found that PolyJet and SLA can meet the required accuracy for clinical applications. Kwon et al [17] studied the accuracy of a 3D-printed patient-specific implant. The shape datasets are extracted from CT images.…”
Section: Related Workmentioning
confidence: 99%
“…They found that PolyJet and SLA can meet the required accuracy for clinical applications. Kwon et al [17] studied the accuracy of a 3D-printed patient-specific implant. The shape datasets were extracted from CT images.…”
Section: Related Workmentioning
confidence: 99%